2015
DOI: 10.5815/ijcnis.2015.05.08
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Techniques for Overcoming Security Threats in Manets

Abstract: Abstract-In day-to-day communications we may need to establish temporary (ad hoc) connections anytime, anywhere. Data transfer through this ad hoc wireless network is required when it is hard to establish the large infrastructure. In MANETs there are many challenges in terms of deploying security especially when the confidentiality of the data is compromised. If the data is highly confidential, then providing security especially in the malicious environment is really a challenging task. Many researchers have h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Setelah mengidentifikasi node ancaman, elemen reaksi mengoreksi prosedur perutean dan penerusan, aktivitas semacam itu mungkin melibatkan penghindaran rute yang melewati node ancaman yang diidentifikasi atau saling mengecualikan node dari network. Studi (Koul & Sharma, 2015) mencoba untuk menyoroti berbagai masalah keamanan secara komprehensif.…”
Section: B Solusi Untuk Ancaman Keamanan Manetunclassified
“…Setelah mengidentifikasi node ancaman, elemen reaksi mengoreksi prosedur perutean dan penerusan, aktivitas semacam itu mungkin melibatkan penghindaran rute yang melewati node ancaman yang diidentifikasi atau saling mengecualikan node dari network. Studi (Koul & Sharma, 2015) mencoba untuk menyoroti berbagai masalah keamanan secara komprehensif.…”
Section: B Solusi Untuk Ancaman Keamanan Manetunclassified
“…Study [58] attempts to highlight various security issues in comprehensive manner. Koul and Sharma [58], upon extensive review of literature on MANETs security and their solutions, created a summary table-see table 2. Table 2.…”
Section: Solutions To Manets' Security Threatsmentioning
confidence: 99%
“…Table 2. Security Mechanisms used to protect MANETs [58] Further similar reviews can be found in articles [59], [60], [61], [62], [63], [64], [65]…”
Section: Solutions To Manets' Security Threatsmentioning
confidence: 99%
“…In the case, when the rate of the security threats realizat ion is exceeded the reaction rate, the attack is launched on the DCS resources [33]. The analysis of the existing security threats allow determine the risks of safety violations for the co mputer systems resources and determine the countermeasures to neutralize the potential threats, by reducing the security risks to an acceptable level [31].…”
Section: Methods For T He Effects Predicting Of T He Dangerous Acmentioning
confidence: 99%